Safe Transportation of Field Planting Stocks of Sympodial Bamboos with Special Reference to Saplings - Kumar, Adarsh; Jain, S. S. (Indian Forester, 2009)
One of the activities of National Bamboo Mission (NBM-India) involves the production of bamboo planting stocks and raising plantations not only to overcome the shortage of bamboos in the country but also to promote the export of bamboo products. The plantation activities involve safe transportation of bamboo planting stocks from nurseries to planting sites. Their safe transportation from nursery to field planting site is as vital as production of field plantable bamboo saplings in the nurseries. It is absolutely essential that the saplings reach the destination in undamaged and uninjured condition. This is one of the most practical and applied aspect of the plantation technology. The bamboo seedlings/saplings need proper protection against high ambient temperature, gusty wind and mechanical vibrations due to speed of the truck (carrying field planting stocks) during transit. The trucks need to have double layered tarpaulin roofing to protect the planting stocks from heat of the sun; proper ventilation for the respiration by the planting stocks and also to prevent the accumulation of carbon di oxide besides protecting the saplings from the gusty wind. Proper care for the planting stock is also utmost requirement, to maintain sufficient moisture for the plants to maintain uptake of nutrients, during transit. The practice adopted at Forest Research Institute (FRI), Dehra Dun under Indian Council of Forestry Research and Education (ICFRE), Dehra Dun has been described.